Stony coral tissue loss disease accelerated shifts in coral composition and declines in reef accretion potential in the Florida Keys - Toth, Lauren T.; Courtney, Travis A.; Colella, Michael A.; Ruzicka, Rob R. (Frontiers in Marine Science, 2023)
Outbreaks of coral disease have been a dominant force shaping western Atlantic coral-reef assemblages since the late 1970s. Stony coral tissue loss disease (SCTLD) is nonetheless having an unprecedented impact in the region. Whereas numerous studies over the last decade have worked to characterize this novel pathogen and its impacts on coral populations, few have quantified its functional effects on reef ecosystems. Of particular importance is how SCTLD may be impacting the essential reef-accretion process and the myriad ecosystem services it supports. Here, we evaluated the impact of SCTLD on reef-accretion potential by estimating carbonate budgets and taxon-level carbonate production at 43 sites throughout the Florida Keys from 2016−2022. Average regional reef-accretion potential declined from an already low, but positive rate of 0.30 ± 0.16 mm y-1 (mean ± standard error) in 2016 before the disease was first observed, to a state of accretionary stasis (0.08 ± 0.12 mm y-1) by 2022. This 70% relative decline in reef-accretion potential was driven by the loss of reef-building corals, with significant decreases in carbonate production by massive taxa including Colpophyllia natans, Montastraea cavernosa, Pseudodiploria strigosa, Orbicella spp., and Siderastrea siderea, and increasing contributions from less susceptible, weedy taxa including Millepora spp., Agaricia spp., and Porites astreoides. In general, changes in taxon-level carbonate production following the SCTLD outbreak mirror long-term shifts in reef assemblages in response to previous stressors. One striking exception, however, is S. siderea, which had become increasingly dominant in recent decades, but declined significantly in response to SCTLD. Overall, by further decimating the already depauperate reef-building coral populations in the Florida Keys, SCTLD has caused a functionally significant shift in the composition of Florida’s coral-reef assemblages and accelerated the loss of regional reef-building capacity. The dire impacts of the disease in south Florida may serve as an early warning that the persistence of the invaluable ecological and socioeconomic functions coral reefs provide will be increasingly threatened throughout the western Atlantic in the aftermath of SCTLD.